Intelligent Agent Server (NetInt) System - Karapetyan, David A. (Mathematical Problems of Computer Science, 2021)
The paper describes Intelligent Agent Server system, which employs software agents. A detailed description of software agents as well some examples of the system application, particularly intrusion detection in local networks is given